Strategies, methods and tools for managing nanorisks in construction. (May 2015) - de Ipiña, J M López; Vaquero, C; Boutry, D; Damlencourt, J F; Neofytou, P; Pilou, M; Jankowska, E; Larraza, I; Pina, R; Fernández, S; Contreras, S; Romero, A; et al.
Abstract: This paper presents a general overview of the work carried out by European project SCAFFOLD (GA 280535) during its 30 months of life, with special emphasis on risk management component. The research conducted by SCAFFOLD is focused on the European construction sector and considers 5 types of nanomaterials (TiO2, SiO2, carbon nanofibres, cellulose nanofibers and nanoclays), 6 construction applications (Depollutant mortars, selfcompacting concretes, coatings, self-cleaning coatings, fire resistant panels and insulation materials) and 26 exposure scenarios, including lab, pilot and industrial scales. The document focuses on the structure, content and operation modes of the Risk Management Toolkit developed by the project to facilitate the implementation of "nano-management" in construction companies. The tool deploys and integrated approach OHSAS 18001 - ISO 31000 and is currently being validated on 5 industrial case studies.